2002
DOI: 10.1021/jf011598c
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Enzymatic Degradability of Xylem and Nonxylem Walls Isolated from Alfalfa Internodes

Abstract: During plant maturation, degradability of alfalfa (Medicago sativa L.) stems declines due to accumulation of highly lignified xylary tissue. Xylem and nonxylem tissues dissected from lower alfalfa internodes were analyzed for cell wall constituents and degradability. Cell walls comprised 740 mg g(-1) of xylem and 533 mg g(-1) of nonxylem tissues. Xylem tissues contributed about 60% of the cell wall mass in internodes. Xylem walls contained 28% lignin, 4% pectin, 29% hemicellulose, and 39% cellulose as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…The inverse correlation seen for the lignin content or the absorbance assigned to aromatics with the levels of cellulose conversion is in close agreement with data reported in previous studies by Grabber et al . [29] for mature and immature alfalfa fibers, Jung and Casler [27] for maize stems at various stages of maturation, Chen and Dixon [30] for transgenic alfalfa, and Lee et al . [31] for selectively delignified wood.…”
Section: Resultsmentioning
confidence: 99%
“…The inverse correlation seen for the lignin content or the absorbance assigned to aromatics with the levels of cellulose conversion is in close agreement with data reported in previous studies by Grabber et al . [29] for mature and immature alfalfa fibers, Jung and Casler [27] for maize stems at various stages of maturation, Chen and Dixon [30] for transgenic alfalfa, and Lee et al . [31] for selectively delignified wood.…”
Section: Resultsmentioning
confidence: 99%
“…Internodal cell walls are comprised to a large extent of highly lignified xylem vessels as compared to the non-xylem vessels. In previous work on alfalfa (Grabber et al, 2002), it was found that the xylem portion of the internodes was rather difficult to hydrolyze compared to the non-xylem portion. This may be due to restricted degradation of xyloglucan in the primary and secondary cell walls, due to greater interaction with lignin.…”
Section: Compositional Effectmentioning
confidence: 99%
“…9 Moreover, improved digestibility in less lignified immature grasses when compared with mature lignified plants has previously been demonstrated. 12 Additionally, studies by Lam et al 8 with 150 lines of forage grass (Phalaris aquatica) and the internodes of 100 lines of ryegrass (Lolium perenne) demonstrated that the hydroxycinnamic acid content was also important to explain the recalcitrance of such grasses.…”
Section: Introductionmentioning
confidence: 99%